Analisis Kemampuan Pemecahan Masalah Siswa dalam Menyelesaikan Soal Matematika pada Materi Kubus dengan Metode Pembelajaran Problem Based Learning di SMPK St Paulus Karuni - Yawu, Yoas Gali; Lede, Yulius Keremata; Kii, Wilhelmus Yape (Lembaga Intelektual Muda (LIM) Maluku, 2023)
This study aims to determine the problem-solving ability of SMPK St. Paul Karuni students in problems. This research method is descriptive qualitative. The subjects of the study were taken by 3 students from 35 students of grade VII B SMPK St. Paul Karuni. with high, medium, and low categories. Based on the type of data obtained from student test results, problem-solving ability in solving math problems on cube material, and interviews with three samples. The data were analyzed based on indicators of polya's problem-solving ability. Data analysis is carried out based on the stages of data reduction, data presentation and conclusion. Based on the results of the study, it can be concluded that 1) the ability to understand the problem, where students are able to write what is known in the question and write down what is asked in the question, 2) the ability to make a solution plan, where students are able to write the formula for solving the problem. 3) the ability to carry out completion, where students can substitute in the form of mathematics and perform calculations. 4) the ability to look back, where students can rewrite the final answer. The factors in students who are unable to solve problems are not understanding the questions well, not focusing on solving problems, not understanding the material taught during learning activities, not having the ability to do the right solution, and not good counting skills